PLATELET COUNT-AGNOSTIC METHODS OF TREATING MYELOFIBROSIS - DONAHUE RAFE MICHAEL JOSEPH; KLENCKE BARBARA JANE; SMITH GREGG DAVID (2021)
Reanalysis of the SIMPLIFY 1 and 2 trials data indicates MMB is effective in JAKi-naive patients and in second line therapy to RUX, providing benefits of reducing enlarged spleens, improving myelofibrosis-related symptoms, and increasing transfusion independence in patient at risk for thrombocytopenia from the underlying disease and RUX therapy. Accordingly, methods of treating myeloproliferative neoplasms (MPN) such as myelofibrosis are described. The methods can include administering a therapeutically effective amount of momelotinib or a pharmaceutically acceptable salt thereof to a subject identified as having (i) myelofibrosis and (ii) a platelet count of less than 150 * l09/L. Also described are methods including administering to a subject with myelofibrosis a therapeutically effective stable dose of momelotinib or a pharmaceutically acceptable salt thereof, for a period of a plurality of weeks, where the subject is assessed as maintaining a platelet count above a predetermined threshold platelet count d